A Case for Providing Electricity Subsidies In Urban Informal Settlements - Ambole, Amollo; Njoroge, Peris; Anditi, Christer; Outa, George (University of Nairobi, 2020)
This policy brief highlights research findings from a two-year project using Nairobi’s Mathare settlement as a case study. The research established that close to 93 per cent of the residents have access to electricity. However, 50 per cent of the connections are informal or illegal, meaning that they are not provided directly by the mandated electric power supply agency: the Kenya Power and Lighting Company, and are thus not metered.
Keywords: Kenya